Pengelolaan Tata Ruang Kantor dalam Mendukung Efektifitas dan Efesiensi Kerja Karyawan Sempoa SIP Medan - Sinaga, Hotdalince; Wira, Teguh Satya (Program Pascasarjana STIE Amkop Makassar, 2024)
Office layout or commonly known as Layot is one of the support work systems that must be considered in the office. Office space arrangement is a necessity of all offices in Indonesia today. The purpose of this study is to find out the management of office space in supporting the effectiveness and efficiency of employee performance, obstacles in the implementation of office space planning and planning that will be carried out in managing office space in the employee performance research of Sempoa Sip Medan. The place of research conducted by the author is at the office of Sempoa Sip Titi Kuning Medan. The place of research conducted by the author is at the office of Sempoa SIP Medan which is located at Jalan Brigjen Zein Hamid Km 6 No.08, Titi Kuning, Kec.Medan Johor, Medan City, North Sumatra 20146. The type of data used by the researcher in this study is qualitative data. The method of data collection techniques can be carried out by interviews, observations. The results of the study show that the office spatial planning in Sip Medan Abacus has gone quite well although there are still some shortcomings. However, it is still carried out with a strategy in the preparation of the layout of office facilities.